Exploring The Role of Green Trust, Subjective Norms and Collectivism on Green Purchase Intention - Judijanto, Loso; Kushariyadi, Kushariyadi; Nurdiani, Tanti Widia; Suryanto, Ardiansyah Bagus; Sari, Titis Nistia; Wijayanthi, Ida Ayu Trisna (Journal of Social Science and Business Studies, 2025)
Green product shopping behavior is considered very important to maintain the sustainability of the earth and human life, the same spirit is not yet shared by the entire community. The more consumers realize the importance of environmentally friendly shopping behavior, the more positive impact it will have on the effectiveness of environmental conservation efforts. Several factors that can influence the intention to buy green products are green trust, subjective norms and collectivism. This study aims to examine the role of each independent variable on the intention to buy green products. This study uses a qualitative method with a literature review, where researchers conduct a study of previous studies that discuss the role of each independent variable, namely green trust, subjective norms and collectivism, both partially and collectively in influencing the intention to buy green products. This study concludes that there is a positive influence of green trust, subjective norms and collectivism both partially and simultaneously on green purchase intention.